AKT regulates hemocyte proliferation via glucose metabolism in Eriocheir sinensis. Issue 127 (August 2022) - Wang, Yue; Nan, Xingyu; Hao, Shuqi; Zhao, Ke; Guo, Yanan; Wang, Qun; Li, Weiwei
Abstract: Threonine-serine protein kinase (AKT) plays an important role in the regulation of essential biological processes such as cell metabolism and cell proliferation in several organisms. Eriocheir sinensis is a widely distributed crab that is exposed to complex and diverse biological environments and various diseases. We aimed to elucidate the immune function of AKT and the underlying mechanism in E. sinensis. In this study, we performed bioinformatics analysis of E. sinensis AKT ( Es Akt) and found that the AKT protein was highly conserved across species. qRT-PCR showed high AKT expression in the liver and muscle tissues, and low expression in hemocytes. After stimulation with gram-positive Staphylococcus aureus or gram-negative Vibrio parahaemolyticus, E. sinensis AKT ( Es Akt) was significantly up-regulated in hemocytes. Further, knockout of the E sAkt gene weakened cell glucose metabolism and inhibited cell proliferation. Taken together, these results suggest that Es Akt plays a key role in regulating hemocyte glucose metabolism and cell proliferation in Eriocheir sinensis . Highlights: Akt mediates cell growth, apoptosis, and proliferation. Bioinformatics analysis of E. sinensis Akt ( Es Akt) showed high conservation. Bacterial stimulation altered Es Akt expression. Es AKT expression is positively correlated with cell metabolism and proliferation. Es Akt could regulate cell proliferation via metabolic reprogramming.